Light–Matter Interaction in Black Phosphorus Coupled to a Si Photonic Crystal at Near Infrared Band - Qin Lu; Cizhe Fang; Yan Liu; Genquan Han; Jincheng Zhang; Yue Hao (IEEE Photonics Journal, 2019)
In this paper, we demonstrate the light interaction mechanism of black phosphorus (BP) in two different structures: the photonic crystal waveguide (PCW) and photonic crystal mirror (PCM). The optical characteristics are simulated by the numerical method finite difference time domain. Specifically, the coupled mode theory is used to investigate the light propagation in PCW structure integrated with BP. By optimizing the geometric parameters, an enhanced light absorption in BP with the maximum of 36.8% at 1550 nm could be obtained. Additionally, with the assistance of BP film, the ultracompact PCM used for a 90° bend connection can achieve a high-reflective efficiency at ∼94% for transverse electric (TE) mode incidence. It is demonstrated that these interesting structures can offer a new way to develop ultracompact photonic integrations based on two-dimensional materials at near infrared field.